Comparison on Tamil and Sinhala Phonological Structure for Second language teaching and learning process. - Wimal, S. (University of Jaffna., 2014)
Phonological knowledge of the Second language is a basic need in both teaching and learning process. Sinhala and Tamil languages are very closed relative languages in Sri Lankan context. Historically in Sri Lankan society Sinhala and Tamil languages have rich language contact mutually. This article attempt to make comparative analysis on phonological structure of both languages for better understanding of the Sinhala and Tamil languages for achievement the goals of second language Teaching and learning process. In vowels level there are two vowels with short and long pronunciation in Sinhala dissimilar compare to Tamil. In consonants level dissimilarities are very high in Sinhala than Tamil. Sinhala Nasalized consonants and Aspiration consonants are very unfamiliar to Tamil native speakers. In this context learning and teaching process of the Sinhala as a second language facing more difficulties in Identification and pronunciation of Sinhala consonants.
Keywords: Phonology; Second Language; Sinhala; Tamil; Teaching and learning.